Mesenchymal stromal cells for acute graft‐versus‐host disease: response at 1 week predicts probability of survival. (13th January 2019) - Galleu, Antonio; Milojkovic, Dragana; Deplano, Simona; Szydlo, Richard; Loaiza, Sandra; Wynn, Robert; Marks, David I.; Richardson, Deborah; Orchard, Kim; Kanfer, Edward; Tholouli, Eleni; Saif, Muhammad; et al.
Summary: Mesenchymal stromal cells (MSCs) have been successfully used for the treatment of steroid‐resistant graft‐versus‐host‐disease (GvHD). However, the lack of early predictors of clinical responses impacts on the time at which to add further treatment and consequently the design of informative clinical trials. Here, we present the UK experience of one of the largest cohorts of GvHD patients undergoing MSC infusions so far reported. We show that clinical responses assessed as early as 1 week after MSC infusion predict patients' overall survival. In our cohort, cell dose, patients' age and type of organ involvement are crucial factors associated with clinical responses.